2020
DOI: 10.1002/ece3.6668
|View full text |Cite
|
Sign up to set email alerts
|

Leaf size variations in a dominant desert shrub, Reaumuria soongarica, adapted to heterogeneous environments

Abstract: The climate in arid Central Asia (ACA) has changed rapidly in recent decades, but the ecological consequences of this are far from clear. To predict the impacts of climate change on ecosystem functioning, greater attention should be given to the relationships between leaf functional traits and environmental heterogeneity. As a dominant constructive shrub widely distributed in ACA, Reaumuria soongarica provided us with an ideal model to understand how leaf functional traits of desert ecosystems responded to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 70 publications
1
6
0
Order By: Relevance
“…Stepwise regression analyses further indicated that variation in leaf length variation was mainly affected by latitude. These indicate that R. soongarica preferentially changes leaf length to adjust leaf size to cope with environmental change (Fan et al, 2020). Low salt stress condition (200 mM) signifcantly promoted the vegetative growth in total leaf area, total fresh weight, and root shoot ratio of R. soongorica seedlings .…”
Section: Physiological Levelmentioning
confidence: 80%
See 1 more Smart Citation
“…Stepwise regression analyses further indicated that variation in leaf length variation was mainly affected by latitude. These indicate that R. soongarica preferentially changes leaf length to adjust leaf size to cope with environmental change (Fan et al, 2020). Low salt stress condition (200 mM) signifcantly promoted the vegetative growth in total leaf area, total fresh weight, and root shoot ratio of R. soongorica seedlings .…”
Section: Physiological Levelmentioning
confidence: 80%
“…Morphological traits: Drought is one of the detrimental environmental stresses that affect morphological growth in plants. Fan et al (2020) used 30 wild populations of R. soongarica and 16 populations grown in a common garden as material to reveal the influence of genetic and ecological factors on leaf morphology. The study revealed that leaf length, width, and leaf length to width ratio (L/W) of the northern lineage were significantly larger than other genetic lineages based on principal component analysis.…”
Section: Physiological Levelmentioning
confidence: 99%
“…Specifically, annual average temperature and annual average precipitation are highly correlated with latitude, and are thought to be important drivers underlying the relationship between leaf traits and latitude [40]. As early as the 19th century, biogeographers noticed that leaves in low latitudes were usually larger in size [41], with leaf size decreasing with increases in altitude [42]. However, the relationship between leaf size and environmental factors is not fixed, and may vary in different regions or different species [41].…”
Section: Introductionmentioning
confidence: 99%
“…As early as the 19th century, biogeographers noticed that leaves in low latitudes were usually larger in size [41], with leaf size decreasing with increases in altitude [42]. However, the relationship between leaf size and environmental factors is not fixed, and may vary in different regions or different species [41]. Leaf area and specific leaf area (SLA) are related to plant photosynthesis and primary productivity, which is very important for understanding plant responses to climate change [43]; while leaf nutrient content affects nutrient cycling in forests [37].…”
Section: Introductionmentioning
confidence: 99%
“…While the variability is most often related to functions of photosynthesis [2,6,7] and drought response [8][9][10], leaves have been shown to display variability as a result of numerous climatic influences, including temperature [11][12][13], precipitation [14][15][16] and light conditions [17][18][19][20]. Additionally, the influence of latitude [21,22] and altitude gradient [3] on variations in leaf morphology has been proven. The underlying mechanisms of adaptation are both anatomical and physiological.…”
Section: Introductionmentioning
confidence: 99%